Description of the Distribution and Characteristics of Leptospirosis Sufferers in Bantul Regency 2023 - Dewantari, Ihsanti (Jurnal Riset Kesehatan Masyarakat, 2024)
ABSTRACT Background: Leptospirosis is a zoonotic disease that causes morbidity and death. Leptospirosis cases continue to increase  in the Special Region of Yogyakarta so that it is designated as an endemic area. Bantul Regency is a district with a high level of endemic leptospirosis cases in Yogyakarta. Based on a data report from the Bantul Regency Health Office, the number of cases in 2020 was 49 cases with 1 death case and in 2021 there were 45 cases. Although it has decreased, cases began to increase again in 2022 to reach 100 cases. This study aims to determine the distribution and characteristics of leptospirosis sufferers in Bantul Regency in 2023. Methods: The type of research is observational descriptive research with a cross sectional approach. The sample in this study is all leptospirosis cases in Bantul Regency throughout 2023 with a total of 111 sufferers. Data was obtained from the Bantul Regency Health Office and interviews with patients were then analyzed univariately. Results: The results of the study showed that the cases were spread across the districts of Piyungan, Banguntapan, Kasihan, Sewon, Bantul, Jetis, Bambanglipuro, Pundong, and Srandakan. Most leptospirosis patients in Bantul Regency are male (73.9%), >46 years old (68.5%), have a junior high school education (40.5%), and work as farmers (32.4%). Conclusions:  Leptospirosis cases are spread across 9 sub-districts out of 17 sub-districts in Bantul Regency and most of the male sufferers, aged >46, have a history of last junior high school education, and work as farmers.Keywords:leptospirosis, gender, age